Kangquan Recipe Regulates the Expression of BAMBI Protein via the TGF-β/Smad Signaling Pathway to Inhibit Benign Prostatic Hyperplasia in Rats. (2nd May 2019) - Chen, Wenfan; Huang, Xiaoqing; Peng, Axiang; Chen, Tingting; Yang, Renzhi; Huang, Yuanpeng; Yang, Zongbao; Xi, Shengyan
Abstract : Background . Kangquan Recipe (KQR) is a traditional Chinese medicine compound made by our research group for the treatment of benign prostatic hyperplasia (BPH). Whether KQR can treat BPH as a single drug or play a role in the treatment of BPH in combination therapy needs further study. Aim of the Study . To investigate the effect of KQR on the expression of TGF- β /Smad signaling pathway-related factors in rats with BPH. In-depth analysis revealed the relevant signal transduction mechanism by which KQR acts to treat BPH. Materials and Methods . Forty-eight male Sprague-Dawley rats were randomly divided into six groups of 8 rats each. In addition to the control group, 40 rats were castrated and then injected with testosterone propionate to form a prostatic hyperplasia model. After 30 days, three groups received different concentrations of KQR (14 g/kg, 7 g/kg, and 3.5 g/kg), and the finasteride group received 0.5 mg/kg finasteride. The BPH group and the control group received the same volume of saline. All groups were treated for a total of 30 days. Rat body weight, prostate volume, wet weight, index, histology, and the mRNA and protein levels of TGF- β, TGF- β R1, TGF- β R2, p-Smad2, p-Smad3, BAMBI, E-cadherin, and N-cadherin in the prostate tissue were measured after the end of treatment. Results . Compared with the control group, the BPH group had increased prostate wet weight, volume, and index, and the histology showed significant BPH. Compared with the BPH group, the three KQR groups and the finasteride group all had varying levels of reduction in the prostate wet weight, volume, and index of the prostate and varying degrees of improvement in the histological manifestations of BPH. KQR downregulates the mRNA and/or protein expression of TGF- β, TGF- β R1, TGF- β R2, p-Smad2, p-Smad3, and N-cadherin protein in prostate tissue and increases the mRNA and protein expression of BAMBI and E-cadherin protein. Conclusions . In the model of BPH induced by testosterone propionate after castration, KQR can inhibit the conduction of the TGF- β /Smad signaling pathway by upregulating the expression of BAMBI protein and reversing EMT in rat prostate tissue.